Testing the monophyly of the ground-dweller spider genus Harpactea Bristowe, 1939 (Araneae, Dysderidae) with the description of three new species. Issue 7 (15th July 2020) - Platania, Leonardo; Pavlek, Martina; Arnedo, Miquel
Abstract : The genus Harpactea Bristowe, 1939 (Araneae, Dysderidae) is one of the most diverse and abundant components of the Mediterranean ground-dwelling spider fauna. However, the taxonomic boundaries of the genus are unclear and its monophyly has been questioned, yet never tested, in a quantitative framework. The only taxonomic revisions in the genus trace back to the 1960s–1990s, and most subsequent work has consisted of single species descriptions. Part of the confusion surrounding the genus and species groups delimitations have to do with the lack of a standardized nomenclature for diagnostic structures based on explicit homology statements. Here we use the description of new species of Harpactea to propose a set of homologies in the male and female genitalia and a standardized nomenclature for those structures. We formally describe three new Harpactea species: H. salvatorei sp. nov., from a cave in the north-eastern Italian Alps, and H. damini sp. nov. and H. mateparlovi sp. nov. from different caves on the Biokovo Mountain and surroundings in Croatia. All the new taxa belong to the lepida species group. In addition, we use a multilocus target gene approach to provide the first hypothesis on the internal phylogenetic structure of the genus Harpactea and the subfamily Harpacteinae, which includes representatives of all currently accepted species groups in the genus and genera in the subfamily. Our results support the close affinities of the species here described but reject the monophyly of both Harpactea and some of the species groups proposed in the literature. http://zoobank.org/NomenclaturalActs/bd2739c9-c1f0-451f-88cc-06c784987a62 http://zoobank.org/NomenclaturalActs/ffb50b2e-ac7b-49a8-aa0d-408143c8a990 http://zoobank.org/NomenclaturalActs/184c58fe-6501-4cc2-ba50-cca4fcff8289